Behavioural measures of child's eating temperament and their link with BMI. (1st March 2017) - Godefroy, Valérie; Trinchera, Laura; Darcel, Nicolas; Rigal, Natalie
Abstract: Rothbart's model of temperament, defined as individual differences in reactivity and self-regulation, has a strong heuristic value with applications in a wide variety of children's outcomes. Our objective was to test Rothbart's model applied to children's food behaviours and BMI outcome through behavioural measures. Our hypotheses, according to Rothbart's model, were as follows: (i) self-regulation in eating modulates appetite reactivity; (ii) appetite reactivity increases the risk of excess BMI, whereas self-regulation in eating limits this risk. One hundred and four children aged between 7 and 12 years completed four behavioural tasks to assess scores for two components of appetite reactivity (i.e. appetite arousal and appetite persistence) and two components of self-regulation in eating (i.e. self-regulation in eating without hunger and self-regulation in eating speed). Their heights and weights were measured in order to calculate their BMI-for-age. T-tests and regression analysis were used to verify our hypotheses. None of the scores of self-regulation in eating was directly associated with BMI but we observed a significant impact of self-regulation in eating without hunger on appetite arousal ( p-value  = 0.04), together with a modest but significant association between appetite persistence and BMI ( p-value  = 0.02). We can thus conclude that our behavioural measures could be used for the determination of the child's eating temperament. Further studies are needed to investigate how to use these measures to improve the treatment of overweight in children.